A pilot study of the efficacy and safety of bolus administration of alteplase in acute myocardial infarction. Issue 2 (August 1991) - Gemmill, J D; Hogg, K J; MacIntyre, P D; Booth, N; Rae, A P; Dunn, F G; Hillis, W S
Abstract : OBJECTIVE--To examine the efficacy, safety, and the pharmacokinetic profile of a bolus dose administration regimen of alteplase in the treatment of acute myocardial infarction. DESIGN--An open pilot study. SETTING--District general hospital. PATIENTS--33 suitable consecutive patients presenting within six hours of the onset of symptoms who satisfied the electrocardiographic criteria for acute myocardial infarction. INTERVENTIONS--Two intravenous boluses of 35 mg alteplase, 30 minutes apart. MAIN OUTCOME MEASURES--Angiographic coronary patency at 90 minutes and 24 hours. Plasma alteplase concentration-time profile and pharmacokinetic analysis. RESULTS--Coronary patency at 90 minutes: 26 of 30 arteries (87%, 95% confidence interval (CI) 74-99%). Coronary patency at 24 hours: 24 of 29 arteries (83%, CI 69-97%). Mean (SD) plasma tissue plasminogen activator (t-PA) concentration reached 4434.8 (2117.8) and 4233.3 (2217.5) ng/ml within 10 minutes of each bolus and fell to 425.8 (288.3) ng/ml between boluses. The estimated peak concentrations at two minutes after boluses were 12, 389 (8580) ng/ml and 10, 811 (6802) ng/ml. The derived pharmacokinetic variables were volume of distribution 3.11 (1.89) 1, clearance 21.3 (9.3) 1/h, half life 5.9 (1.7) minutes. CONCLUSIONS--This simple administration regimen achieved brief, high concentrations of plasma t-PA that were well tolerated. The regimen was associated with a high coronary patency rate at 90 minutes that was well maintained at 24 hours.